Stalinist city planning : professionals, performance, and power - DeHaan, Heather D., 1974- (University of Toronto Press, 2013)
"Based on research in previously closed Soviet archives, this book sheds light on the formative years of Soviet city planning and on state efforts to consolidate power through cityscape design. Stepping away from Moscow's central corridors of power, Heather D. DeHaan focuses her study on 1930s Nizhnii Novgorod, where planners struggled to accommodate the expectations of a Stalinizing state without sacrificing professional authority and power. Bridging institutional and cultural history, the book brings together a variety of elements of socialism as enacted by planners on a competitive urban stage, such as scientific debate, the crafting of symbolic landscapes, and state campaigns for the development of cultured cities and people. By examining how planners and other urban inhabitants experienced, lived, and struggled with socialism and Stalinism, DeHaan offers readers a much broader, more complex picture of planning and planners than has been revealed to date."--Jacket.